1999
DOI: 10.1006/jcis.1999.6346
|View full text |Cite
|
Sign up to set email alerts
|

AC Electric-Field-Induced Fluid Flow in Microelectrodes

Abstract: During the AC electrokinetic manipulation of particles in suspension on microelectrode structures, strong frequency-dependent fluid flow is observed. The fluid movement is predominant at frequencies below the reciprocal charge relaxation time, with a reproducible pattern occurring close to and across the electrode surface. This paper reports measurements of the fluid velocity as a function of frequency and position across the electrode. Evidence is presented indicating that the flow occurs due to electroosmoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
450
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 465 publications
(463 citation statements)
references
References 8 publications
12
450
0
1
Order By: Relevance
“…This type of particle aggregation was concluded to not arise from positive DEP, but possibly to be influenced by electrophoretic effects. However, Green and Morgan 80 and Ramos et al 81 correctly interpreted this effect in terms of a hydrodynamic fluid flow induced by electro-osmotic stress arising from the interaction of the electric field and the electrical double layer on an electrode surface. Anomalous frequency effects, not explainable by DEP forces alone, were also observed by Voldman et al 67 for particles held in traps, and this was also attributed to electrohydrodynamic flow.…”
Section: Technologymentioning
confidence: 99%
“…This type of particle aggregation was concluded to not arise from positive DEP, but possibly to be influenced by electrophoretic effects. However, Green and Morgan 80 and Ramos et al 81 correctly interpreted this effect in terms of a hydrodynamic fluid flow induced by electro-osmotic stress arising from the interaction of the electric field and the electrical double layer on an electrode surface. Anomalous frequency effects, not explainable by DEP forces alone, were also observed by Voldman et al 67 for particles held in traps, and this was also attributed to electrohydrodynamic flow.…”
Section: Technologymentioning
confidence: 99%
“…Induced-charge electro-osmotic flows driven by applied AC fields can thus persist only in a certain band of driving frequencies, τ −1 e ≤ ω ≤ τ −1 c , unless Faradaic reactions occur at the electrodes to maintain the bulk field. In AC electro-osmosis at adjacent surface electrodes (Ramos et al (1999)) or AC pumping at an asymmetric electrode array (Ajdari (2000)), the inducing surfaces are the electrodes, and so the two time scales coincide to yield a single characteristic frequency ω c = 1/τ e . (Note that Ramos et al (1999) and Gonzalez et al (2000) use the equivalent form ω ∼ σλ D /ε w L.) Table 2 presents typical values for ICEO flow velocities and charging time scales for some reasonable microfluidic parameters.…”
Section: Double-layer Relaxation At Electrodesmentioning
confidence: 99%
“…Although ICEO flows have been observed in diverse settings [1,5,8,9], ICEP motion of colloids is largely unexplored. In what may be the only prior experimental work, Murtsovkin and Mantrov [10] observed that the motion of quartz particles of irregular shapes varies with the square of the applied field, but did not provide a theory.…”
mentioning
confidence: 99%